2010
DOI: 10.1177/155005941004100407
|View full text |Cite
|
Sign up to set email alerts
|

EEG Topography and Tomography (LORETA) in Diagnosis and Pharmacotherapy of Depression

Abstract: Earlier investigations suggested an involvement of the right hemisphere and the left prefrontal cortex (PFC) in the pathogenesis of depression. This paper presents our own electroencephalographic (EEG) topography and low-resolution brain electromagnetic tomography (LORETA) data obtained in unmedicated depressed patients, and the effects of two representative drugs of non-sedative and sedative antidepressants, i.e., citalopram (CIT) and imipramine (IMI), as compared with placebo in normal subjects. Sixty female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 44 publications
3
58
0
2
Order By: Relevance
“…More directly, EEG studies have indicated that depressed patients have a negative asymmetry index in alpha power, reflecting left frontal hypo-and right frontal hyper-activation. The more negative the asymmetry index in the frontal lobes, the more severe are the depressive symptoms [49]. The abnormal structural asymmetry of the DLPFC found in our study is consistent with the view that depression is associated with an inter-hemispheric imbalance.…”
Section: Discussionsupporting
confidence: 80%
“…More directly, EEG studies have indicated that depressed patients have a negative asymmetry index in alpha power, reflecting left frontal hypo-and right frontal hyper-activation. The more negative the asymmetry index in the frontal lobes, the more severe are the depressive symptoms [49]. The abnormal structural asymmetry of the DLPFC found in our study is consistent with the view that depression is associated with an inter-hemispheric imbalance.…”
Section: Discussionsupporting
confidence: 80%
“…Los incrementos en la densidad de corriente prevalecieron en las bandas alfa y theta, lo que coincide con los resultados observados en las MEBAs 20 y en algunos estudios con LORETA en pacientes deprimidos. 21 El objetivo del presente trabajo fue estudiar los cambios en las fuentes de EEG, según el método VARETA, en un grupo de pacientes con trastorno depresivo mayor que recibieron EMTr a 5Hz sobre la corteza prefrontal dorsolateral izquierda como tratamiento único o en combinación con escitalopram, un inhibidor selectivo de la recaptura de serotonina.…”
Section: 11unclassified
“…Responders and non-responders differ in QEEG measurements at rest and during taskoriented activities (Bruder et al, 2008). LORETA, which assesses activity of deeper cortical regions like ACC and orbitofrontal cortex (Pizzagalli et al, 2001), identifies cortical alterations in relation to depression and antidepressant response (Anderer et al, 2002;Saletu et al, 2010). Both cordance and LORETA require whole-head electrode montages for data collection, which entails up to 75 minutes of QEEG recording, limiting its clinical utility.…”
Section: Neurostructural and Neurofunctional Studiesmentioning
confidence: 99%